Dostępność źródeł kapitału w warunkach funkcjonowania polskich przedsiębiorstw - Zygmunt, Aleksandra (Availability of Capital Sources in the Conditions of Polish Companies Functioning, 2006)
This article shows the possibilities of capital gaining by Polish companies. It also indicates the main sources of capital with its availability, with particular consideration to profit, credits, venture capital, emissions of shares, bonds, leasing, factoring and also franchising
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 761-768